Alpha2‐adrenoceptor agonists in small animal practice 1. Why they do what they do. Issue 9 (4th October 2013) - Flaherty, Derek
Abstract : Alpha2 ‐adrenoceptor agonists are widely used for premedication, sedation and, more recently, provision of analgesia in small animal practice. However, although these drugs may offer significant benefits over alternative agents, they also have a number of side effects that must be appreciated. This, the first in a series of two articles, explains how the pharmacology of these drugs leads to both the desirable and adverse effects observed with these agents. The second article, which will be published in a forthcoming issue of In Practice, will describe the most appropriate way to use alpha2 ‐adrenoceptor agonists to optimise their clinical effects.